2018
DOI: 10.30773/pi.2018.06.07
|View full text |Cite
|
Sign up to set email alerts
|

Avoidant Insecure Attachment as a Predictive Factor for Psychological Distress in Patients with Early Breast Cancer: A Preliminary 1-Year Follow-Up Study

Abstract: ObjectiveTo identify attachment insecurity as an associative factor with unresolved psychological distress 1 year after surgery in the early breast cancer (BC) population. MethodsOne-hundred fourteen participants completed the Hospital Anxiety and Depression Scale (HADS) and the Experiences in Close Relationship (ECR-M36) questionnaire within 1 week (baseline) and at 1-year post-surgery (follow-up). Participants were categorized into the distress and the non-distress groups based on a HADS-total score cut-off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The protective impact of attachment security on physical and psychological distress of cancer patients has been demonstrated by an increasing number of publications. Low attachment security, conceptualized and measured as attachment anxiety and attachment avoidance, is closely associated with symptom burden and pain, depression and anxiety, and existential distress, 8 , 16–18 as well as impaired communication between patients and their medical caregivers 19 ,. 20 Evidence suggests that these associations may be due to the difficulties of patients with low attachment security to experience supportive and meaningful interpersonal relationships 9 ,.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective impact of attachment security on physical and psychological distress of cancer patients has been demonstrated by an increasing number of publications. Low attachment security, conceptualized and measured as attachment anxiety and attachment avoidance, is closely associated with symptom burden and pain, depression and anxiety, and existential distress, 8 , 16–18 as well as impaired communication between patients and their medical caregivers 19 ,. 20 Evidence suggests that these associations may be due to the difficulties of patients with low attachment security to experience supportive and meaningful interpersonal relationships 9 ,.…”
Section: Introductionmentioning
confidence: 99%
“…Although the consistent positive effects for attachment security and perceived relatedness on existential distress in patients with cancer have been shown, 7 , 8 , 16 , 18 results are mostly based on cross‐sectional studies in which these constructs are highly correlated. There are only few prospective or even longitudinal studies investigating underlying relationships between those concepts 17 ,. 23 Moreover, the relative contribution of attachment security remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The time since diagnosis ranged from 1-week post-surgery to 5 years, whereas two studies did not report information regarding the time since diagnosis (Ávila et al, 2015 ; Jang et al, 2015 ). The majority of the studies were cross-sectional ( n = 5) and used a convenience sample, while three studies had a longitudinal design with three (Brédart et al, 2015b ; Favez & Cairo Notari, 2021 ) and two (Lee et al, 2018 ) measurement points, respectively. All the studies were published in journals.…”
Section: Resultsmentioning
confidence: 99%
“…We used the Modified Experiences in Close Relationships Scale (ECR-M16) to measure participants’ experiences in close romantic and nonromantic relationships across two domains: attachment anxiety and attachment avoidance [ 29 , 30 ]. This is a shortened version of the ECR-M36, and existing research has found the ECR-M36 to be a useful tool for understanding attachments to close family, friends, and medical staff during the course of serious illness [ 31 , 32 ]. The ECR-M16 contains 16 items scored on a 7-point Likert scale ranging from 1 (“disagree”) to 7 (“agree”), with total scores ranging from 8 to 56 on each subscale.…”
Section: Methodsmentioning
confidence: 99%